Suitability of Hemophagocytic Syndrome who had a graft rejection for repeat transplantation - Khadeeja Khan, Muhammad Faisal Aslam, Javeria Ghafoor, Muhammad Immran, Nimrah Ishaque,. Ashja Saleem, Maheen Rana (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hematopoietic stem cell transplantation (HSCT) is a crucial treatment for hemophagocytic lymphohistiocytosis, with reduced-intensity conditioning transplantation (RIC) being a superior strategy. Aim: Engraftment failure is a significant challenge, necessitating additional HSCT so a case study involved ten patients who experienced engraftment failure and hemophagocytic syndrome after initial HSCT. Place & duration of study: Chughtai Institute of Pathology, Lahore from March 2018 and January2023 Results: The study found that all five subjects who underwent a second allo-HSCT achieved rapid hematopoietic restoration, with ANC levels above 0.5 108 /L for granulocytes and 20 108 /L for platelets. After transplantation, three individuals experienced acute graft-versus-host disease (aGVHD) of varying severity, with a 60% prevalence and a median onset time of 26 days. Two patients managed their conditions with methylprednisolone, while two patients underwent treatment with second-line anti-GVHD medicine. Implication: A study reveals that second allogeneic hematopoietic stem cell transplantation (allo-HSCT) can restore hematopoietic tissue in failed engraftment patients, particularly those with acute Graft-Versus-Host Disease (aGVHD). Conclusion: A trial evaluating allogeneic hematopoietic stem cell transplantation (allo-HSCT) for engraftment failure in liver and heart failure patients showed a 80% success rate. Further studies are needed to predict success factors for a second allo-HSCT treatment, but the consensus is strong for its potential in treating hemophagocytic disorders. Keywords Implantation failure, hematopoietic stem cell transplantation, Second allogeneic, Hemophagocytic syndrome